The Role of Sustainability Performance and Accounting Assurors in Sustainability Assurance Engagements - Hummel, Katrin (Journal of business ethics, 2019)
Research on sustainability assurance is still in its beginnings. One of the key questions in this field that also is of the highest practical relevance is concerned with the quality of the assurance process. However, a common understanding of assurance quality and how it should be measured is still missing. We try to close this gap by building on the financial audit literature. We introduce a definition of assurance quality that comprises two key aspects: the depth of the assurance process and the breadth of the assurance statement. Based on prior research, we hypothesize that a firm’s sustainability performance is related to the depth of the assurance process, while the type of the assurance provider, more precisely the affiliation to the accounting profession, is related to the breadth of the assurance statement. Results for a sample of 122 European firms reveal a negative relationship between sustainability performance and assurance process depth as well as between the affiliation to the accounting profession and assurance statement breadth. Thus, we find evidence that poor sustainability performers ask for in-depth assurance services, most likely as a means to enhance their internal sustainability-related processes and systems. Assurance providers that do not belong to the accounting profession in turn are associated with broader assurance statements.